1999
DOI: 10.1034/j.1399-3003.1999.14a26.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for the development of respiratory distress syndrome and transient tachypnoea in newborn infants

Abstract: Respiratory distress syndrome (RDS) and transient tachypnoea (TT) are the most frequent acute respiratory diseases in the newborn. This study investigated the risk factors for RDS and TT in newborn infants.A population of 63,537 newborns was enrolled in a 12-month survey in Italy, 734 (1.15%) affected by RDS and 594 (0.93%) affected by TT. Multivariate regression analysis of maternal and perinatal data and the calculation of odds ratios (with 95% confidence intervals) were performed.It was demonstrated that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
115
3
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(147 citation statements)
references
References 24 publications
27
115
3
2
Order By: Relevance
“…EuroNeo Net figures for 2010 show an incidence of 92 % at 24-25 weeks of gestation, 88 % at 26-27 weeks, 76 % at 28-29 weeks and 57 % at 30-31 weeks [1,2]. Prematurity is the main cause of RDS [3]. The basic physiopathologies of RDS are mulifactorial including impaired gas exchange, decreased static compliance, and alveolar collapse due to the lack of surfactant, pulmonary edema caused by disruption of alveolo-capilar membrane integrity and finally lung injury [1,4].…”
Section: Introductionmentioning
confidence: 99%
“…EuroNeo Net figures for 2010 show an incidence of 92 % at 24-25 weeks of gestation, 88 % at 26-27 weeks, 76 % at 28-29 weeks and 57 % at 30-31 weeks [1,2]. Prematurity is the main cause of RDS [3]. The basic physiopathologies of RDS are mulifactorial including impaired gas exchange, decreased static compliance, and alveolar collapse due to the lack of surfactant, pulmonary edema caused by disruption of alveolo-capilar membrane integrity and finally lung injury [1,4].…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were observed in the study done by Dani C, where it was observed that mothers >32 years of age were at a higher risk of delivering babies with respiratory distress. 8 …”
Section: Maternal Agementioning
confidence: 99%
“…13 However in the study done by Dani C, it was observed that that there is no significant association with respiratory distress and the sex of the baby. 8 …”
Section: Baby Sexmentioning
confidence: 99%
See 1 more Smart Citation
“…Criteria used to diagnose or label a neonate having TTN were clinical signs of respiratory distress (tachypnea, grunting, nasal flaring, retractions and cyanosis), tachypnea which persisted 48-72 hours, chest X-ray consistent with TTN (hyperaeration, perihilar streaking, flattening of diaphragm and pleural or interstitial fluid) and absence of any diagnosis leading to respiratory distress. 19 Neonates with hypoglycemia, hypocalcemia, polycythemia, meconium aspiration, any congenital cardiac, respiratory or central nervous system malformation, septicemia and birth asphyxia were excluded. Controls were classified as neonates born at term gestation by elective LSCS due to one of similar sets of indications in mothers as of cases and who did not develop respiratory distress and had no other indication for admission at birth.…”
Section: Methodsmentioning
confidence: 99%